Pemanfaatan Alat Permainan Edukatif Botol Angka Dalam Menstimulasi Perkembangan Anak Usia Dini - Aghnaita Aghnaita; Sri Hidayati; Ervina Ervina; Devi Oktavia (Pakis Journal Institute, 2024)
Early childhood development is crucial in a child's life. One of them is by stimulating children through the number bottle educational game tool. These educational game tools can develop fine motor and cognitive development in early childhood. The purpose of this community service activity is to assist in utilizing the number bottle educational game tool in stimulating early childhood development in Yasalmuna Palangka Raya Islamic Kindergarten. The method used is the service learning method through lectures and demonstrations. The subjects in the activity were 17 students at Yasalmuna Palangka Raya Islamic Kindergarten. The result of this activity is that children can demonstrate the number bottle educational game tool well. In addition, children's abilities in fine motor and cognitive development can also be seen.